(untitled) (REMUNOM, 2024)
eam as a whole being imperative. This includes adapting curricula and resuming attention and care actions, demanding a practice that encompasses health promotion, protection, and recovery, in addition to all the logistical, supply, and management issues inherent to the profession. Objective: to reflect on the profile of pharmacists in Caruaru, Pernambuco, and the context in which they operate. Furthermore, the aim is to discuss, based on other works available in the literature, the social and historical factors related to the identity of this professional. Methods: This study was conducted from April 17 to 30, 2021. A semi-structured, self-administered, anonymous questionnaire with 14 questions was used as the data collection instrument, addressing variables related to education and professional field, as well as basic aspects such as age, gender, and satisfaction level with the Regional Pharmacy Council. The population consisted of pharmacists residing in the city of Caruaru, Pernambuco. Results: 85% of the respondents are female. 80.8% have a postgraduate specialization degree. 50% of the participants stated that they work in community/commercial pharmacies, and 38.5% in the public service. Conclusion: The study operates under the perspective that gaining a better understanding of professionals’ profiles and their ways of operating under social conditions determined by the institutions they work for can provide a foundation for overcoming existing obstacles, ensuring that the roles of pharmacists are meaningful and ethical within the professional practice.